Water-induced reordering in ultrathin ionic liquid films. (26th July 2018) - Henderson, Z; Walton, A S; Thomas, A G; Syres, K L
Abstract: Water-induced reordering in ultrathin ionic liquid films has been observed using in situ x-ray photoelectron spectroscopy. An ultrathin layer of 1-butyl-3-methylimidazolium tetrafluoroborate ([C4 C1 Im][BF4 ]) was deposited on a rutile TiO2 (1 1 0) single crystal and exposed to water vapour at a relative humidity of ~70% in an in situ cell. Water was found to adsorb onto the ionic liquid surface, causing a reordering of the ions at the interface. Water initially remained trapped on the ionic liquid surface as the in situ cell was evacuated. This could have negative implications for supported ionic liquid phase catalysis, where reactants and products move in and out of an ionic liquid containing the catalyst. This insight into the behaviour at the water/ionic liquid interface provides a basis for understanding interfacial behaviour in more complex gas/ionic liquid systems.